Geographical Distribution and Driving Meteorological Forces of Facial Expressions of Visitors in Urban Wetland Parks in Eastern China - Li, Hongyan; Wang, Xuege; Wei, Hongxu; Xia, Tingting; Liu, Mengnan; Ai, Shengshu (Frontiers in Earth Science, 2022)
Interacting with aquatic environments in blue spaces is believed to benefit mental well-being. Relevant understanding is limited to regional pilot studies using self-reported emotions on questionnaires. We assessed emotional response by rating facial expressions on a large geographical scale with the purpose of detecting a relationship to microclimates. A total of 920 facial photos were collected from Sina Weibo from 20 wetland parks in 14 eastern cities of China during 2020. Daily average air temperature, rainfall, average relative humidity (RH), and wind velocity were also recorded from the days when photos were posted on-line. We found that happy expressions were higher in wetlands of eastern cities than in northern and inland cities. Sad expressions varied statistically among wetland locations. Weather records differed between temperate and subtropical climatic zones and were highly varied among cities. Happy and sad scores were driven by the change of average air temperature. Combined multivariable regression and binomial correlation suggested that increasing air temperature would not evoke positive emotions unless higher than 11.5 °C, and an air temperature range of 17.5–22.3 °C will be optimum to induce the presentation of a smile face. Air humidity generally imposed a negative effect on expressions of positive emotions. Further verification of our findings is suggested on a larger geographical scale using more powerful big-data to obtain more robust conclusions.